Ranking Influential Factors on Job Satisfaction Based on University Students' Perspective - Pham, Yen Thi Hong; Doan, Thao Bich; Tran, Huyen Thu; Nguyen, Huyen Thi; Pham, Anh Viet; Tran, Thang Xuan; Nguyen, Ngoc Thi Hong (Frontier Management Science, 2024)
This study utilizes Herzberg's Two-Factor Theory to quantitatively analyze university students' perspectives on future work motivation. Addressing the challenges in securing and sustaining meaningful employment, the research focuses on the impact of motivators on job attraction. A structured survey collects data from a representative sample of university students to quantify relationships between specific motivators and overall job attraction. Anticipated findings contribute empirical insights into the unique dynamics of youth employment, refining Herzberg's theory in this context. Implications extend to informing organizational practices, policies, and interventions for enhancing the job satisfaction and well-being of young workers.